5G INTEGRATED MOBILE SATELLITE SERVICE WITH HIGH ENERGY EFFICIENCY - Chen, Joy Iong-Zong (IRO Journal on Sustainable Wireless Systems, 2019)
Communication technology is moving towards its next generation network and 5G implementation. 5G provides high resource efficiency, continuity, reduced power consumption and increased resilience. This technology is integrated with mobile satellite service (MSS). This new architecture improves the commercial value proposition of the network, provide optimal performance and energy efficiency. It improvises the ubiquity, mobility, broadcast and security features of the existing communication system. It also provides an efficient broadband connectivity in moving platforms and good broadcast services. The long propagation delay of MSS is also addressed in this paper. We also the meet the increased backhaul demands thereby saving physical sites on ground.